2005
DOI: 10.1529/biophysj.105.068551
|View full text |Cite
|
Sign up to set email alerts
|

Second Virial Coefficient Studies of Cosolvent-Induced Protein Self-Interaction

Abstract: Protein self-interaction is important in protein crystal growth, solubilization, and aggregation, both in vitro and in vivo, as with protein misfolding diseases, such as Alzheimer's. Although second virial coefficient studies can supply invaluable quantitative information, their emergence as a systematic approach to evaluating protein self-interaction has been slowed by the limitations of traditional measurement methods, such as static light scattering. Comparatively, self-interaction chromatography is an inex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 52 publications
5
58
0
Order By: Relevance
“…B-value experiments performed on approximately 70 different aqueous and membrane proteins clearly demonstrate the potential of the values as a diagnostic for initial crystallization conditions as well as for improving existing crystallization conditions (Berger et al, 2005(Berger et al, , 2006Dumetz et al, 2007;García, Hadley et al, 2003;Patro & Przybycien, 1996;Pjura et al, 2000;Tessier & Lenhoff, 2003;Tessier, Vandrey et al, 2002;Valente et al, 2005). However, in spite of the demonstrated capability of SLS B-value measurements to serve as a diagnostic for solution conditions that are more likely to result in crystals, this experimental approach has not gained traction within the crystallographic community.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…B-value experiments performed on approximately 70 different aqueous and membrane proteins clearly demonstrate the potential of the values as a diagnostic for initial crystallization conditions as well as for improving existing crystallization conditions (Berger et al, 2005(Berger et al, , 2006Dumetz et al, 2007;García, Hadley et al, 2003;Patro & Przybycien, 1996;Pjura et al, 2000;Tessier & Lenhoff, 2003;Tessier, Vandrey et al, 2002;Valente et al, 2005). However, in spite of the demonstrated capability of SLS B-value measurements to serve as a diagnostic for solution conditions that are more likely to result in crystals, this experimental approach has not gained traction within the crystallographic community.…”
Section: Reviewmentioning
confidence: 99%
“…The experiments shown here took approximately 20 min to generate a value for B, compared with Comparison of SIC (blue diamonds) and SLS data for lysozyme as a function of NaCl concentration. The data are taken from the following references: blue diamonds, Valente et al (2005); red squares, García, Holman et al (2003); green triangles, Guo et al (1999); purple circles, . several hours for each SLS data point.…”
Section: Reviewmentioning
confidence: 99%
“…Valente et al [13] have reported that sugars (e.g. sucrose) influence the conformational dynamics of proteins, favoring the most compact conformation within the native-state ensembles.…”
Section: Effect Of Various Pharmaceutical Excipients (Sucrose and Glymentioning
confidence: 99%
“…sucrose) influence the conformational dynamics of proteins, favoring the most compact conformation within the native-state ensembles. This reduction of protein volume is accompanied by a concomitant reduction in the hydrophobicity of the protein surface, thus reducing the tendency for protein-protein self association [13]. Kaushik and Bhat [98] have pointed out to another possible stabilization mechanism that has to be considered.…”
Section: Effect Of Various Pharmaceutical Excipients (Sucrose and Glymentioning
confidence: 99%
See 1 more Smart Citation